2013
DOI: 10.1038/hdy.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Rapid range expansion increases genetic differentiation while causing limited reduction in genetic diversity in a damselfly

Abstract: Many ectothermic species are currently expanding their geographic range due to global warming. This can modify the population genetic diversity and structure of these species because of genetic drift during the colonization of new areas. Although the genetic signatures of historical range expansions have been investigated in an array of species, the genetic consequences of natural, contemporary range expansions have received little attention, with the only studies available focusing on range expansions along a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 65 publications
(92 reference statements)
5
84
1
1
Order By: Relevance
“…This implies a northward shift of the summer temperature needed to enable Pacific oyster spawning in wild populations. This will further push the distribution range of the Pacific oyster northward into previously unfavourable areas/ecosystems, as previously documented for other species [63]. Our findings of a theoretical possible increased supply of foreign C .…”
Section: Discussionsupporting
confidence: 72%
“…This implies a northward shift of the summer temperature needed to enable Pacific oyster spawning in wild populations. This will further push the distribution range of the Pacific oyster northward into previously unfavourable areas/ecosystems, as previously documented for other species [63]. Our findings of a theoretical possible increased supply of foreign C .…”
Section: Discussionsupporting
confidence: 72%
“…; Swaegers et al . ). Allelic surfing can thereby generate false positive signatures of selection (Excoffier & Ray ; Excoffier et al .…”
Section: Introductionmentioning
confidence: 97%
“…As study species we chose the poleward range‐expanding damselfly Coenagrion scitulum (Swaegers et al. ). We have previously shown that this species evolved a faster life history (Therry et al.…”
Section: Introductionmentioning
confidence: 99%